Cell-free microbial culture filtrates as candidate biostimulants to enhance plant growth and yield and activate soil- and plant-associated beneficial microbiota - Morcillo, Rafael Jorge León; Baroja-Fernández, Edurne; López-Serrano, Lidia; Leal-López, Jesús; Muñoz, Francisco José; Bahaji, Abdellatif; Férez-Gómez, Alberto; Pozueta-Romero, Javier (Frontiers in Plant Science, 2022)
In nature, plants act as metaorganisms, hosting microorganisms that communicate with the plants by exchanging semiochemicals through the phytosphere. Such symbiotic interactions are of high importance not only for plant yield and quality, but also for functioning of the soil microbiota. One environmentally sustainable practice to increasing crop productivity and/or protecting plants from (a)biotic stresses while reducing the excessive and inappropriate application of agrochemicals is based on the use of inoculants of beneficial microorganisms. However, this technology has a number of limitations, including inconsistencies in the field, specific growth requirements and host compatibility. Beneficial microorganisms release diffusible substances that promote plant growth and enhance yield and stress tolerance. Recently, evidence has been provided that that this capacity also extends to phytopathogens. Consistently, soil application of microbial cell-free culture filtrates (CFs) has been found to promote growth and enhance the yield of horticultural crops. Recent studies have shown that the response of plants to soil application of microbial CFs is associated with strong proliferation of the resident beneficial soil microbiota. Therefore, the use of microbial CFs to enhance both crop yield and stress tolerance, and to activate beneficial soil microbiota could be a safe, efficient and environmentally friendly approach to minimize shortfalls related to the technology of microbial inoculation. In this review, we compile information on microbial CFs and the main constituents (especially volatile compounds) that promote plant growth, yield and stress tolerance, and their effects on plant-associated beneficial microbiota. In addition, we identify challenges and limitations for their use as biostimulants to bring them to the market and we propose remedial actions and give suggestions for future work